2014
DOI: 10.1093/jxb/eru489
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional approaches for studying plant defence against insects: from ecology to omics and synthetic biology

Abstract: The biggest challenge for modern biology is to integrate multidisciplinary approaches towards understanding the organizational and functional complexity of biological systems at different hierarchies, starting from the subcellular molecular mechanisms (microscopic) to the functional interactions of ecological communities (macroscopic). The plant-insect interaction is a good model for this purpose with the availability of an enormous amount of information at the molecular and the ecosystem levels. Changing glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 221 publications
(230 reference statements)
0
55
0
Order By: Relevance
“…What typically distinguishes metabolomics from targeted analyses or general metabolic profiling is the ambition to integrate with other omics sciences (Fiehn, 2002;Barah and Bones, 2015). Combined with the guiltby-association principle (Bino et al, 2004;Saito et al, 2008), omics analyses allow the prediction of unknown gene and metabolite functions.…”
mentioning
confidence: 99%
“…What typically distinguishes metabolomics from targeted analyses or general metabolic profiling is the ambition to integrate with other omics sciences (Fiehn, 2002;Barah and Bones, 2015). Combined with the guiltby-association principle (Bino et al, 2004;Saito et al, 2008), omics analyses allow the prediction of unknown gene and metabolite functions.…”
mentioning
confidence: 99%
“…Understanding plant-pest interactions at a systems level is indispensable to elucidating the mechanisms behind the interactions. However, a combined understanding of how systems components interact to determine the outcome is required for a holistic view of such a complex, multidimensional system and is becoming increasingly important for developing strategies to control existing and emerging pests [6,74]. …”
Section: Host-pest Interactions: Enter Systems Biologymentioning
confidence: 99%
“…Plant-insect interactions are increasingly being investigated using omics technologies [6]. One of the benefits of omics data is that it facilitates analysis of non-model organisms, even in cases where little or no prior knowledge of the system exists [7].…”
Section: Host-pest Interactions: Enter Systems Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…The processes lead to alteration in metabolite pool of affected plants (Ncube, Finnie, & Van Staden, 2012) sometimes causing a negative impact on plant insect interactions (Jamieson et al, 2017), lower plant fitness and affect total cassava starch yields of up to 100% (Nuwamanya et al, 2014). Some studies have reported the complexity of plant responses to combinations of attacks making it impossible to directly infer from pairwise plant-insect interactions (Barah & Bones, 2017).…”
Section: Introductionmentioning
confidence: 99%